2005
DOI: 10.1103/physreva.72.032340
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of a quantum key distribution with two and three mutually unbiased bases

Abstract: We study the robustness of various protocols for quantum key distribution. We first consider the case of qutrits and study quantum protocols that employ two and three mutually unbiased bases. We then derive the optimal eavesdropping strategy for two mutually unbiased bases in dimension four and generalize the result to a quantum key distribution protocol that uses two mutually unbiased bases in arbitrary finite dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For example, under certain postselection strategies, the restriction p(x) = q(x) in theorem 1 may be violated. We will show later that for sifting on orthogonal basis states, the convexity property (22) holds.…”
Section: Properties Of the Mutual Information And The Holevo Quanmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, under certain postselection strategies, the restriction p(x) = q(x) in theorem 1 may be violated. We will show later that for sifting on orthogonal basis states, the convexity property (22) holds.…”
Section: Properties Of the Mutual Information And The Holevo Quanmentioning
confidence: 94%
“…The proof of this theorem is in appendix C. Since we use postselection in our protocols, we need to extend these theorems to hold for the key rater(E(ρ AB )) in the following sensē r(E(ρ AB )) ≤ λr(E(ρ AB )) + (1 − λ)r(E(σ AB )). (22) This property (22) does not hold in general. For example, under certain postselection strategies, the restriction p(x) = q(x) in theorem 1 may be violated.…”
Section: Properties Of the Mutual Information And The Holevo Quanmentioning
confidence: 99%
“…In high-dimensional systems, complementary observables and the corresponding MUBs have been exploited to enhance the security in quantum cryptograpy [7], perform fundamental tests of quantum mechanics, such as quantum contextuality [8][9][10], explore logical indetermi-nacy [11], and several other tasks in quantum information. For instance, new quantum key distribution protocols were conceived in which a larger error rate can be tolerated while preserving security [12,13]. Moreover a different protocol extending Ekert91 [14] by using entangled qutrits has been experimentally realized [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, new quantum key distribution protocols were conceived in which a larger error rate can be tolerated while preserving security1213. Moreover a different protocol extending Ekert9114 by using entangled qutrits has been experimentally realized15.…”
mentioning
confidence: 99%
“…In particular, it has been shown that an increase in the dimension leads to a better performance of various quantum information protocols, such as for example quantum cryptography [4][5][6] and some problems in distributed quantum computing [7]. Moreover, a relevant experimental effort has been recently spent in the generation, manipulation and detection of quantum systems with higher dimension [8,9].…”
Section: Introductionmentioning
confidence: 99%